The social media life of climate change: Platforms, publics, and future imaginaries. (27th December 2018) - Pearce, Warren; Niederer, Sabine; Özkula, Suay Melisa; Sánchez Querubín, Natalia
Abstract : Social media is a transformative digital technology, collapsing the "six degrees of separation" which have previously characterized many social networks, and breaking down many of the barriers to individuals communicating with each other. Some commentators suggest that this is having profound effects across society, that social media have opened up new channels for public debates and have revolutionized the communication of prominent public issues such as climate change. In this article we provide the first systematic and critical review of the literature on social media and climate change. We highlight three key findings from the literature: a substantial bias toward Twitter studies, the prevalent approaches to researching climate change on social media (publics, themes, and professional communication), and important empirical findings (the use of mainstream information sources, discussions of "settled science, " polarization, and responses to temperature anomalies). Following this, we identify gaps in the existing literature that should be addressed by future research: namely, researchers should consider qualitative studies, visual communication and alternative social media platforms to Twitter. We conclude by arguing for further research that goes beyond a focus on science communication to a deeper examination of how publics imagine climate change and its future role in social life. This article is categorized under: Perceptions, Behavior, and Communication of Climate Change > Communication Abstract : Composite image representing the visual vernacular of influential climate change organizations on Facebook, comprising the most engaged with climate change images posted on the platform. Visual research and the production of new visual research products is one way of expanding our knowledge of the social media life of climate change, beyond dominant methods which focus on text. Design: Beatrice Gobbo, Andrea Benedetti and Federica Bardelli. Source : Pearce et al. (2018).